KEPUASAN KERJA SEBAGAI PEMEDIASI PADA PENGARUH KOMPENSASI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DI UMKM JAVA LOENPIA - Aprilia, Nia; Rr. Hawik Ervina Indiworo; Rita Meiriyanti (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
The research object took the Java Loenpia Semarang UMKM on the grounds that there was a problem, namely that the income target set by the management was not able to be realized from October 2022 to September 2023, this shows that the target and realization of income were not in line with the expectations of the UMKM leadership, so a strategy was needed to increase employee performance. This research aims to analyze the influence of compensation and work environment on employee performance with job satisfaction as a mediating variable in Java Loenpia Semarang MSMEs. The research sample was 70 respondents/employees of Java Loenpia Semarang MSMEs using sampling techniques, namely population research or census techniques or saturated samples. The data analysis method uses multiple linear regression. The research results found that compensation and work environment partially influence job satisfaction. Compensation, work environment and job satisfaction partially influence employee performance. The results of the findings of the first mediation effect can be concluded that there is no influence of compensation on employee performance with Job Satisfaction as a mediating variable. Meanwhile, the findings of the second mediation effect can be concluded that there is an influence of the work environment on employee performance with Job Satisfaction as a mediating variable